Pemberdayaan Masyarakat Melalui Pembentukan Bank Sampah Untuk Meningkatkan Ekonomi Masyarakat Desa Wirittasi - Al-Idrus, Syarifah Khusnul Khotimah; Nasruddin, Nasruddin; Santi, Hanida Aulia; An-Nafi, Anastasya Rosyida; Aulia, Siti; Arifin, Akhmad Nabil; Hardiansyah, Hardiansyah; Muhammad, Muhammad; Zaini, Fakhruz; Hidayatullah, Muhammad Syarif; Mukminin , Amirul; Padly, Asse; Amin, Ainol; Rosanti , Amelia; Maulana, Firman; Jazuli, Muhammad Sulaiman; Atiqah, Adinda Nur (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
The empowerment of Zero Waste Maritime Village Caring for the Marine Environment Based on Creative Economy was organized by the PPK Ormawa HMG Team, Lambung Mangkurat University through education, training, and mentoring methods to the people of Wirittasi Village. With this program, it is hoped that the community can realize the potential of waste in Wirittasi Village. The results of the activity show that the community already has knowledge and skills in managing waste in Wirittasi Village, through waste sorting activities and the 3R Movement which has been held as one of the community empowerment media by the Ormawa HMG PPK TEAM. The establishment of waste banks in partner villages is one of the targets pursued by the Ormawa HMG PPK TEAM so that village communities have a place to be able to manage their waste for sale to provide environmental and economic benefits for the community. If continued, this program will improve the economic opinion of the community through waste management activities by the community. To maintain the sustainability of the program, it is necessary to implement further programs, and the participation of village and local governments as facilitators for this community empowerment activity is needed.